2006
DOI: 10.1016/j.fcr.2005.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Variability of root length density and its contributions to seed yield in chickpea (Cicer arietinum L.) under terminal drought stress

Abstract: The importance of root systems in acquiring water has long been recognized as crucial to cope with drought conditions. This investigation was conducted to: (i) evaluate the variability on root length density (RLD) of chickpea in the vegetative growth stage; (ii) estimate the effect of RLD on seed yield under terminal drought conditions; and (iii) set up a procedure to facilitate the screening of chickpea genotypes with large RLD. Twelve diverse chickpea genotypes were grown in tall PVC cylinders with two diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
206
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 233 publications
(224 citation statements)
references
References 30 publications
10
206
1
2
Order By: Relevance
“…Under terminal drought, total root biomass of chickpea at an early stage of growth was shown to contribute to yield at maturity in a previous work, particularly by maximizing transpiration over evaporation of water stored into the surface layers (15 to 30 cm) of the soil profile (Kashiwagi et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…Under terminal drought, total root biomass of chickpea at an early stage of growth was shown to contribute to yield at maturity in a previous work, particularly by maximizing transpiration over evaporation of water stored into the surface layers (15 to 30 cm) of the soil profile (Kashiwagi et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…Tall PVC cylinder system was optimized for use to estimate the chickpea root growth since the rooting profi le can not be estimated in shallow pot-grown plants. When the plants were grown in PVC cylinders 18 cm in diameter and 120 cm in height, fi lled with a sand-vertisol mixture containing a soil moisture equivalent to 70% field capacity, the extracted root biomass was demonstrated to be signifi cantly correlated to the ones extracted from the field (r = 0.62, p < 0.05) (Kashiwagi et al, 2006). With this system, the sampling effi ciency could be improved dramatically up to about 25 profiles worker -1 day -1 .…”
Section: Current Research Status On Drought Avoidance Root Traits In mentioning
confidence: 99%
“…Under waterlimited receding soil moisture conditions, the root system that can extract relatively more water from deeper soils and/or absorb water relatively rapidly (thereby maximizing transpiration over evaporation) can increase total water transpired. Increased transpiration is not only expected to increase the total biomass productivity but also improves the harvest index (Passioura, 1977(Passioura, , 1994Kashiwagi et al, 2006). In several crops, such as common bean (White and Castillo, 1990), groundnuts (Wright et al, 1991) and soybean (Cortes and Sinclair, 1986), deep rooting has been demonstrated to have positive effects on seed yield through improved transpiration.…”
Section: Grain Yield Under Soil Moisture-stress Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction in cortical cell size and number, lignification of epidermal and exodermal cells and layering of sclerenchymatous cells in neighbour of cortical cells are due to the deposition of lignin, and suberins is one of another modifications under water deficit condition [13]. Drought tolerant cultivars tend to have a greater root biomass, i.e., a greater root-to-shoot ratio and deeper root profiles in common beans and pea [14], cowpea [15], soy bean, pea and chickpea [16]. A high ratio of deep root weight to shoot weight was also found to maintain high plant water potentials and had a positive effect on yield under stress [17].…”
Section: David Publishingmentioning
confidence: 99%